Pemanfaatan Tari Tradisional dalam Menanamkan Nilai Budaya pada Anak Usia Dini - Diana Siregar; Eka Damayanti Hasibuan; Fadiah Dian Nasfati; Yasmina Fajri; Hilda Zahra Lubis (CV Edujavare Publishing, 2025)
This study aims to describe the use of traditional dance as a medium in instilling cultural values ​​in early childhood at TK Ilmi Insani Medan. The background of this study is the importance of preserving culture from an early age and efforts to instill national character through an art approach that is appropriate to child development. The method used is a qualitative approach with observation, interview, and documentation techniques. The results of the study show that traditional dance is used not only as a means of entertainment, but also as an educational medium that introduces values ​​such as cooperation, discipline, respect, and love for local culture. Teachers have a central role in designing contextual and enjoyable learning through dance activities. In conclusion, the use of traditional dance is very effective in supporting character formation and cultural understanding in early childhood.